Tyrannosaur [videorecording (DVD)] - Considine, Paddy; Considine, Paddy; Marsan, Eddie; Colman, Olivia; Mullan, Peter (Strand Releasing, 2012)
Joseph is an unemployed widower, drinker, and a man crippled by his own volatile temperament and furious anger. Hannah is a Christian worker at a charity shop, a respectable woman who appears wholesome and happy. When the pair is brought together, Hannah appears as Joseph's potential savior, someone who can temper his fury and offer him warmth, kindness, and acceptance. As their story develops, Hannah's own secrets are revealed and Joseph becomes her source of comfort.